Sun Bathing Affects Overweight-Obese Subjects Vitamin D Deficiency - Rio yudistira christanto; Andriati; Dwikora Novembri Utomo; Indrayuni Lukitra Wardhani (Surabaya Physical Medicine and Rehabilitation Journal, 2022)
Background: There are increasing number of studies that discuss the effect of sun exposure to overweight and obese individuals with vitamin D deficiency (which is UVB exposure can increase serum 25-Hydroxyvitamin D levels). However, until now there is no a literature review about these studies. This shows a weak correlation between sun bathing and serum 25-Hydroxyvitamin D elevation in overweight and obese people. Aim: Describe the effect of the sun bathing for overweight-obese patient with vitamin D deficiency. Material and Methods: Electronic searching tools (ScienceDirect, Pubmed, and Google Scholar) were conducted from the 1990s until the recent literature. A sensitive search strategy uses specific terms. Studies were included if the population with BMI > 25 Kg/m2; Sun Exposure intervention, the studies provided the comparison of implementation method, the studies provided 25-Hydroxyvitamin D status as the outcome. For the exclusion criteria: studies that included subjects metabolics syndrome. MMAT was used for eliminating biased research. Results: Two studies were fulfilled our inclusion criteria. The studies, were excluded, mainly because they lacked data, biased reseach, and failure to answer any authors questions. Conclusion: The sun exposure method has a positive corellation for increasing serum 25-Hydroxyvitamin D level in overweight and obese subjects with vitamin D deficiency, but internal factors (age and skin color) and external factors (season, temperature, dose, and duration) need to be considered to get effective result. Keywords: Obese, Overweight, Sun bathing, Vitamin D deficiency, 25-Hydroxyvitamin D.